Ex vivo normothermic preservation of a kidney graft from uncontrolled donation after circulatory death over 73 hours - Montagud-Marrahi, Enrique; Luque, Yosu; Ros, Ruben Rabadan; Ajami, Tarek; Cuadrado-Payan, Elena; Estrella, Hector; Arancibia, Andres; Sánchez-Etayo, Gerard; Bohils, Marc; Marrero, Ramsés; Fundora, Yilliam; Ramírez-Bajo, Maria José; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The transplant community is focused on prolonging the ex vivo preservation time of kidney grafts to allow for long-distance kidney graft transportation, assess the viability of marginal grafts, and optimize a platform for the translation of innovative therapeutics to clinical practice, especially those focused on cell and vector delivery to organ conditioning and reprogramming. We describe the first case of feasible preservation of a kidney from a donor after uncontrolled circulatory death over a 73-h period using normothermic perfusion and analyze hemodynamic, biochemical, histological, and transcriptomic parameters for inflammation and kidney injury. The mean pressure and flow values were 71.24 ± 9.62 mmHg and 99.65 ± 18.54 mL/min, respectively. The temperature range was 36.7°C–37.2°C. The renal resistance index was 0.75 ± 0.15 mmHg/mL/min. The mean pH was 7.29 ± 0.15. The lactate concentration peak increased until 213 mg/dL at 6 h, reaching normal values after 34 h of perfusion (8.92 mg/dL). The total urine output at the end of perfusion was 1.185 mL. Histological analysis revealed no significant increase in acute tubular necrosis (ATN) severity as perfusion progressed. The expression of KIM-1, VEGF, and TGFβ decreased after 6–18 h of perfusion until 60 h in which the expression of these genes increased again together with the expression of β-catenin, Ki67, and TIMP1. We show that normothermic perfusion can maintain a kidney graft viable ex vivo for 3 days, thus allowing a rapid translation of pre-clinical therapeutics to clinical practice.